The Battlefield Behind Bars: How Mental Disorder and Suicidal Behavior Impacts the Prison Experience for Veterans - Morgan, Mark Alden (American journal of criminal justice, 2019)
Military veteran status has been associated with a variety of criminal justice outcomes as well as higher rates of mental illness and suicide when compared to the general population. Although research has generally focused on why veterans become involved with the justice system, less is known about their experiences while incarcerated. In particular, studies of veterans in the community context indicate that they are unwilling to seek out mental health treatment due to potential stigmas, suggesting that this reluctance may extend into the prison environment. Using a sample of 14,278 veteran and nonveteran inmates, we find that veterans do not necessarily fare worse in prison and are actually more likely to obtain treatment. However, this effect is largely mediated by the greater history of mental disorders and suicidal behaviors among veterans. Our findings lend credence to recent efforts designed to screen and manage justice-involved veterans as a distinct, at-risk group.